Infective Endocarditis: Clinical Characteristics and Echocardiographic Findings - Poorzand, Hoorak; Hamidi, Fatemeh; Sheybani, Fereshte; Ghaderi, Fereshteh; Fazlinezhad, Afsoon; Alimi, Hedieh; Bigdelu, Leila; Khosravi Bizhaem, Saeede (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Infective endocarditis (IE) remains a disease with high morbidity and mortality. The aim of this study was to determine the clinical characteristics and echocardiographic features of patients with IE. Methods: We analyzed patients with either definitive or probable diagnosis of IE who were hospitalized in a teaching hospital in Mashhad, Iran between June 2011 to January 2020. Patients who survived were followed up by echocardiography for at least 6-month after hospital discharge. Results: A total of 82 cases with IE were included of which 62 (75.6%) received definitive diagnosis. The mean age was 39.7±18.7 years and 52 (63.4%) were male. The most common preexisting structural cardiac abnormality that predispose patients to IE were congenital heart diseases (28 %) of which bicuspid aortic valve was more common (n=12, 14.6 %), followed by ventricular septal defect (n=9, 11 %) and tetralogy of Fallot (TOF) (n=2, 2.4%). Three (3.6 %) cases had rheumatic heart disease and 12 (14.6 %) were injecting drug users. The most common causative pathogen was Staphylococcus aureus, detected in 7 (19.4%) cases. Follow-up echocardiography revealed right or left ventricular failure in 10 (12.1%) cases. Cardiac complications occurred in 41 (50%) cases and systemic complications in 63 (76.8%). All-cause mortality was 34 (41.5%) and 6 (18.1%) died due to cardiovascular complications. Conclusions: The short- and long-term prognosis in IE was poor and the predictors for in-hospital and 1-year mortality were defined as heart failure and septic shock. Congenital heart disease and intravenous illicit drug using (IVDU) were the most common predisposing condition which may necessitate a revision in the IE prophylaxis recommendations.